KISAH-KISAH DALAM AL-QUR'AN PERSPEKTIF PENDIDIKAN ISLAM - Humaedah Humaedah (PAI RAFAH, 2021)
Al-Quran in the holy book as well as a guide for life in the world for muslims. There are so many exclamations in the verses of the koran that contain educational values, one of which is through the stories of previous people. This paper aims to review how to recognize the stories in the Koran, the kinds of stories, the storytelling techniques, and what educational value they contain. The method used in this paper is a research library with a philosophical approach that functions to conduct content analysis through conceptual and linguistic analysis. Literature study using books, articles and various relevant journals as data sources, then analyzed and set forth in a narrative form. The results of this study conclude that the stories in the Al-Quran are the history of those that tell about the events of the prophet and apostles, as well as the previous people. The story contains moral advice which can be used as a guide for the daily life of Muslims, which is written in an interesting manner. There are several educational values in the story of the Koran, including the value of religious education, the value of intellectual education and the value of moral education. In Addition, Al-Quran stories can be used as a learning method through interesting and media.